Carbon nanomaterials : modeling, design, and applications - Zhou, Kun (Chemist) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"The book analyzes in-depth the most important carbon nanomaterials, including fullerenes, carbon nanotubes, graphene and novel carbon nanomaterial-based membranes and thin films, with emphasis on modeling, design and applications. The fundamental relationship between the structures of materials and their properties are illustrated from both the experimental and modeling aspects. Advanced applications in tribology, biomedical devices, energy storage and conservation and environmental treatments are demonstrated. Each chapter is written by experts in the field, which ensures that both a review on the subject and an in-depth discussion of the underlying mechanisms are provided"--
Modeling mechanical properties of graphene-based and diamond-like nanostructures / Dr. Julia A. Baimova and Prof. Sergey Dmitriev -- Anharmonic excitations in graphene and other 2D nanomaterials / Dr. Elena Korznikova and Prof. Sergey Dmitriev -- Modeling thermal properties of graphene and graphene-based nanostructures / Prof. Bo Liu.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials; Carbon; Graphene; Nanotubes; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Material Science